Pola Infestasi Serangan Hama Pada Tanaman Mutan Kedelai Hitam Detam 4 Prida Generasi Tiga (M3): Infestation Patterns of Pest Attack on Black Soybean Detam 4 Mutant Plant on Third Generation (M3) - Septiana Septiana; Siti Novridha Andini; Miranda Ferwita Sari (Politeknik Negeri Lampung, 2022)
The black soybean plant is one of the food crops whose existence is very necessary for the consumption of the population in Indonesia. People of Indonesians very consumted with sweet flavorings, but do not want to make the risk of diabetes. Black soybeans in addition to being the main ingredient in making sweet soy sauce, also has benefits for mothers who are breastfeeding because of the rich nutritional content of benefits for the growth and development of the baby. Due to the high demand for black soybeans, the government encourages farmers to further increase the production of black soybeans. One of the government's efforts is to release the Detam Prida 3 and Detam 4. However, in these production efforts, there are pest to the decline in the quality and quantity of production caused by pest attacks of black soybean plants. The purpose of this study was to determine the pattern of pest infestations on soybean plants both in the vegetative and generative. In this study using Detam Prida 4, observations were carried out every day from the vegetative to the generative. Observations are carried out daily after planting. The observation made is to determine the pattern of attack infestation, which is not harmful to the current condition (+), harm at the time condition (++), and very dangerous at the time (+++). From the results of this study the pests that attack black soybeans in the vegetative phase are seed flies, armyworms, and aphids that attack from the seventh day after planting and pests that attack black soybeans in the generative phase, namely leaf roller caterpillars and green ladybugs that attack 30 days after planting.